Survey On Business Model For Cloud Computing Using Rsa & Aes Algorithm (International Journal of Engineering and Computer Science, 2015)
Storing of confidential data has become a most important thing these days. It is necessary that the data stored must remainsecured and should be accessed at the client’s request. Cloud computing helps us to store our files on the cloud. Hence it is very efficientand helpful for a client’s point of view. But there are some security issues in this type of data storage. Thus by using encryption anddecryption techniques we can encrypt and decrypt the files as per the need of the client.